Community-Based Conservation in the Drylands of East and Southern Africa During COVID-19 (a peer reviewed report) - Mara Goldman; Roque de Pinho, Joana; Kronenburg Garcia, Angela; Gargallo, E.; Heita, J. (Natural Hazards Center Quick Response Grant Report Series, 341, 2022)
Our research focused on dryland communities in conservation landscapes in Namibia, Kenya, and Tanzania, where tourism and community-based conservation have been adopted as market-based solutions to social and environmental vulnerabilities. The COVID-19 pandemic resulted in the cessation of international tourism and the suspension of most employment related to community-based conservation in the region. These disruptions caused devastating impacts on local livelihoods which had become partly dependent on tourism and conservation-related income to meet household needs. We partnered with local co-researchers to document the unfolding impacts of COVID-19 on community members in our study sites using qualitative research methods. More specifically, we examined the following research questions: (a) How were people from different demographic groups (e.g., gender, age, income, conservation employment status) affected by the sudden loss of tourism income and cessation of community-based conservation activities? and (b) How did people across these different demographic groups respond to the loss of conservation and tourism benefits? We found that the pandemic’s effects were unevenly experienced. In Kenya, for example, wealthier community members were able to invest in cattle and profit from pastoralism whereas poorer members struggled to feed their families. Namibia was the lone case in which the government and other organizations implemented measures to support household income. Our diverse findings reveal the value of comparative case studies as well as the need for long-term research to capture the unfolding, quite unpredictable, impacts of the COVID-19 pandemic. Our study also revealed the value and challenge of doing “remote ethnography” in hazards research. https://hazards.colorado.edu/research/quick-response-report/archives